Community Unionism
XIII, 249 p.
Keywords: This book examines the concept of 'community unionism', which argues that the future of the labour movement and industrial relations lies with the community and local labour markets. Providing a conceptual overview of the term, the book uses international case studies and draws on faith-based organizations to explore the issue.